Investigate the relationship of 360-degree emotional intelligence and creativity and innovation of managers in training hospitals of Shiraz University of Medical Sciences in 2013 - Shahabi, Nahid; Miri, Farzaneh; Asadi Pour, Elaheh (Researcher Bulletin of Medical Sciences, 2019)
Introduction Management and human factors are the most important changing which humanity is facing today in all fields and in different form in various communities. Emotional intelligence is one of the applied topics in the field of personnel management and communication. The aim of this study is to determine the correlation between 360-degree emotional intelligence and a creativity and innovation of managers in training hospitals of Shiraz Medical Sciences University. Research Methodology This study is cross-sectional and 71 of the senior and middle managers at training hospitals of Shiraz Medical Sciences were selected as statistical sample. Data collection tool in this study is a questionnaire containing 107 questions and its Cronbach's alpha coefficient was 0.81. Data was analyzed using SPSS 16 software, utilizing t-test statistical tests and Pearson correlation. Results A direct correlation was observed between dimensions of emotional intelligence, i.e. self-management, communication and management were correlated with each other. Another result was a correlation between emotional intelligence, creativity and innovation. (p <0.05) Conclusion This study showed a two-way direct correlation between emotional intelligence and creativity and also emotional intelligence and innovation. Managers can create creativity and innovation or prevent them in employees by their performance.